Kolare, tiggare, spelmän – finnmarken och dess invånare i Dan Andersson författarskap - Kowalska, Magdalena (Folia Scandinavica Posnaniensia, 2007)
Dan Andersson (1888-1920), a poet and writer, has a large number of enthusiasts in Sweden. Many of his poems were put to music and they became well - known songs. His lyrics are said to contain the essence of Sweden - anxiety, melancholy and existential dilemmas. He lived and wrote in the period of important political and social transformations which were also reflected in literature. There are many similarities in the biographies of Dan Andersson and of the first proletariat writers. Being himself very poor he commiserated with the poor, the unhappy and the sufferers. This compassion reflected in his works has taken the form of philosophical and religious thoughts of human fate and attitude towards God. The background of Dan Andersson works is finnmark - a Finnish colony region lying on the border between the province of Varmland and Dalama. When describing his finnmark Dan Andersson combines realistic pictures of hard work, poverty and misery with elements of fantasy and folk beliefs. He also pays a lot of attention to the descriptions of nature. His heroes are very characteristic: they are charcoalburners, beggars, fiddlers, shamans and criminals. Each of these groups is described in a different way.